1982
DOI: 10.1121/1.387342
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical studies for two multiple-channel cochlear implant patients

Abstract: Psychophysical studies were conducted on two multiple-channel cochlear implant patients to examine the nature of the hearing sensations produced by electrical stimulation of auditory nerve fibers using electrodes at different sites in the scala tympani (one electrode at a time). Both time-invariant stimuli, whose parameter values did not vary in time, and time-varying stimuli, specified by a linear variation in parameter values, were used. A sharpness ranking study using time-invariant signals suggested that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 13 publications
6
62
0
Order By: Relevance
“…A number of authors have suggested that psychophysical stimuli can be used to understand individual differences between CI users (Tong et al 1982, Shannon 1983 as well as to probe the detailed effects of CI signal processing (Henry et al 2000). The results from the present study are relevant for CI signal processing developments that attempt to improve CI pitch perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have suggested that psychophysical stimuli can be used to understand individual differences between CI users (Tong et al 1982, Shannon 1983 as well as to probe the detailed effects of CI signal processing (Henry et al 2000). The results from the present study are relevant for CI signal processing developments that attempt to improve CI pitch perception.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Pretorius andHanekom 2008, Goldsworthy et al 2013) have found CI discrimination thresholds between 5 and 30 %; furthermore, Vandali et al (2014) demonstrated that training can improve CI discrimination thresholds by more than a factor of 2. While the use of synthetic tones presented through the CI processor is relatively unexplored, there is a rich literature investigating CI pitch perception based on electrode psychophysics (Tong et al 1982;McDermott and McKay 1997;Hanekom and Shannon 1998;Zeng 2002;Henry and Turner 2003;Carlyon et al 2010;Hughes and Goulson 2011;Goldsworthy and Shannon 2014) as well as using more natural stimuli (Fujita and Ito 1999;Gfeller et al 2002;McDermott 2004;Looi et al 2008). In the present article, the suggestion put forth by Pretorius and Hanekom (2008) that pure and complex tones can be used to probe different aspects of perception is extended toward understanding correlations with phoneme identification in noise.…”
Section: Introductionmentioning
confidence: 99%
“…Previous pitch-ranking studies in traditional cochlear implant users have indicated that both electrode location (place pitch cues) and stimulation rate (temporal pitch cues) can influence the perceived pitch (e.g., Tong et al 1982;Shannon 1983;Townshend et al 1987;McKay et al 2000). For instance, a more basal electrode will elicit a higher pitch than a more apical one, and a higher stimulation rate will elicit a higher pitch than a lower rate, up to around 300 Hz where the rate pitch cue saturates.…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysical studies have revealed that there are two basic cues for pitch perception in cochlear implant subjects (Tong et al 1982;Townshend et al 1987) and that these cues are independent of each other Tong et al 1983). The first cue is related to the site of excitation along the cochlea (place pitch).…”
Section: Introduction and Outlinementioning
confidence: 99%